2011
DOI: 10.1016/j.yhbeh.2011.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Somatic genital reflexes in rats with a nod to humans: Anatomy, physiology, and the role of the social neuropeptides

Abstract: Somatic genital reflexes such as ejaculation and vaginocervical contractions are produced through the striated muscles associated with the genitalia. The coordination of these reflexes is surprisingly complex and involves a number of lumbosacral spinal and supraspinal systems. The rat model has proved to be an excellent source of information regarding these mechanisms, and many parallels to research in humans can be drawn. An understanding of the spinal systems involving the lumbosacral spinal cord, both effer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 126 publications
(150 reference statements)
1
13
0
Order By: Relevance
“…A previous study demonstrated effects of GRP treatment on erectile and ejaculatory reflexes using an ex copula paradigm in spinal intact rats [18]. However, in this paradigm, it is not possible to eliminate actions of GRP on the supraspinal areas that control ejaculation from the spinal ejaculation generator, including the nucleus of the paragigantocellularis (nPGi) [57][58][59], the medial preoptic area (MPOA) [60] and the paraventricular nucleus of the hypothalamus [58,[61][62][63]. Moreover, emissions or ejaculations as observed in the ex-copula paradigm are not dependent on the spinal ejaculation generator [56] as lesions of the LSt cells did not block sexual reflexes using this paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated effects of GRP treatment on erectile and ejaculatory reflexes using an ex copula paradigm in spinal intact rats [18]. However, in this paradigm, it is not possible to eliminate actions of GRP on the supraspinal areas that control ejaculation from the spinal ejaculation generator, including the nucleus of the paragigantocellularis (nPGi) [57][58][59], the medial preoptic area (MPOA) [60] and the paraventricular nucleus of the hypothalamus [58,[61][62][63]. Moreover, emissions or ejaculations as observed in the ex-copula paradigm are not dependent on the spinal ejaculation generator [56] as lesions of the LSt cells did not block sexual reflexes using this paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that OXTR is implicated in female sexual response. Based on data from animal studies, female pelvic organs involved in (pre-) copulatory behavior are provided with OXTR and oxytocin neural fibers descending into the lumbosacral parts of the spinal cord ( 40 , 41 , 42 ). Peripheral and central effects on the pelvic organs are implicated in the preparation for the copulatory activities with regard to lubrication, muscular contractility and pain suppression for the coming vagino-cervical distension ( 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptors have been detected in MPOA, PVN and PAG nuclei, illustrating the strong estrogenic input of these areas. Ascending genitosensory information has been shown to influence these lumbosacral targets either directly or indirectly via brain regions associated with the regulation of sexual behavior, including the oxytocin receptors-containing neurons in the PVN ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were carried out on adult male Wistar rats (12)(13)(14)(15)(16) weeks at the start of the experiment), which were either obtained from Charles River Laboratories (ChRL, Sulzfeld, Germany; experiments 1 and 2) or bred in the animal facilities of the University of Regensburg (UReg), Germany (experiment 3). Stimulus females were obtained from ChRL; their sexual receptivity was reliably induced by SC administration of 50 μg estradiol benzoate dissolved in 0.1-mL corn oil 48 hours prior to testing [29].…”
Section: Animalsmentioning
confidence: 99%
“…The two systems exert their effects through partly overlapping neuronal pathways that include the medial preoptic area (MPOA) in the forebrain [11,12] and the sacral parasympathetic nucleus (SPN) in the spinal cord [13]. In addition, 5‐HT neurons in the nucleus paragigantocellularis (nPGi), which are known to inhibit ejaculation, are innervated by OXT axons [14,15], and OXT neurons in the paraventricular hypothalamic nucleus (PVN) respond to administration of 5‐HT or 5‐HT receptor (5‐HTR) agonists [16]. These findings suggest that OXT and 5‐HT interact on multiple levels, but the mechanisms by which this may affect the ejaculatory threshold are not yet understood [17].…”
Section: Introductionmentioning
confidence: 99%